2010
DOI: 10.1016/j.chemosphere.2010.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The improved phytoextraction of lead (Pb) and the growth of maize (Zea mays L.): the role of plant growth regulators (GA3 and IAA) and EDTA alone and in combinations

Abstract: This investigation was made to examine the role of gibberellic acid (GA(3)), indole-3-acetic acid (IAA) and EDTA in improving phytoextraction of the Pb and plant growth on Pb added soil. GA(3), IAA and EDTA were applied separately and in combinations. GA(3) and IAA were applied as foliar spray and seed soaking. EDTA was applied in single and split doses. Analysis of the Pb in different parts of plant was carried out using atomic absorption/flame spectrophotometer. EDTA significantly reduced the plant growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(90 citation statements)
references
References 19 publications
8
80
0
2
Order By: Relevance
“…The inhibitory effect of heavy metals stress induced by Pb growth parameters of Carum carvi is in agreement with the results obtained by some authors using different plants (Chatterjee et al, 2004;Mishra et al, 2006;Sharma & Dubey, 2005;Hadi et al, 2010;Zhou et al, 2010 and Gupta et Non significant (n.s.) at P > 0.05 Significant ( * ) at P ˂ 0.05…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The inhibitory effect of heavy metals stress induced by Pb growth parameters of Carum carvi is in agreement with the results obtained by some authors using different plants (Chatterjee et al, 2004;Mishra et al, 2006;Sharma & Dubey, 2005;Hadi et al, 2010;Zhou et al, 2010 and Gupta et Non significant (n.s.) at P > 0.05 Significant ( * ) at P ˂ 0.05…”
Section: Discussionsupporting
confidence: 81%
“…Although lead is not an essential element for plants, it is absorbed easily and accumulated in different plant parts (Sharma & Dubey, 2005). It exerts adverse effect on plant growth (Hadi et al, 2010), changes in chemical composition, antioxidant enzymes system (Gupta et al, 2009(Gupta et al, , 2010 and lower uptake of many minerals. Lead can cause various physiological and biochemical dysfunctions of many physiological and biochemical processes such as nitrogen assimilation and photosynthesis, Dubey, 2005 andSeregin &Kosevnikova, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the effect of EDTA was many times higher than other organic ligands (Hadi et al, 2010). Saifullah et al (2010) showed that EDTA was more efficient than CA and sulfur in solubilising Pb from the soil.…”
Section: Effect Of Organic Ligands On Pb Speciationmentioning
confidence: 99%
“…Roots, as a important organs of plants, that could accumulate large amounts of lead (Pb), thereby causing a potential health risk by absorbing from polluted soils [8,19]. Considerable efforts have been reported to investigate Pb stress in roots, such as its accumulation, translocation, physiological and metabolic variations, and cell deposition [1,6,8,16]. Therefore, it is an important step towards being able to control the health risk in pollution condition by understanding the mechanism of Pb accumulation in plants roots.…”
Section: Introductionmentioning
confidence: 99%